Motivation for the Work of ISUZU Car Saleman in Bangkok - Visetwongsa, Pisal; Noppanatwonsakorn, Rachen (Journal of Graduate MCU KhonKaen Campus, 2022)
The objectives of this research were 1) to study the level of work motivation of ISUZU car salespeople in Bangkok; 2) to compare the differences between the work motivation of ISUZU car salespeople in Bangkok and the different factors. salesperson person conducting survey research and using questionnaires to collect data from the sample ISUZU car sales representatives in Bangkok, 302 people, using a systematic random sampling method. by randomly stratified The statistics used in the data analysis were frequency, percentage, mean, standard deviation, test, t-value, and one-way variation. The results showed that 1) The motivation for the work of ISUZU car salesmen in Bangkok is very high. The mean is 3.97. ( =3.97) 2) Salespeople of different genders have different work motivations. Significantly, 0.05 is therefore based on the set assumptions, while gender, age, education level and average monthly income are no different